Short and long term effects of a lifestyle intervention for construction workers at risk for cardiovascular disease: a randomized controlled trial - Groeneveld Iris F; Proper Karin I; van der Beek Allard J; Hildebrandt Vincent H; van Mechelen Willem (BMC Public Health, 2011)
Abstract Background The prevalence of overweight and elevated cardiovascular disease (CVD) risk among workers in the construction industry is relatively high. Improving lifestyle lowers CVD risk and may have work-related benefits. The purpose of the study was to evaluate the effects on physical activity (PA), diet, and smoking of a lifestyle intervention consisting of individual counseling among male workers in the construction industry with an elevated risk of cardiovascular disease (CVD). Methods In a randomized controlled trial including 816 male blue- and white-collar workers in the construction industry with an elevated risk of CVD, usual care was compared to a 6-month lifestyle intervention. The intervention consisted of individual counseling using motivational interviewing techniques, and was delivered by an occupational physician or occupational nurse. In three face to face and four telephone contacts, the participant's risk profile, personal determinants, and barriers for behavior change were discussed, and personal goals were set. Participants chose to aim at either diet and PA, or smoking. Data were collected at baseline and after six and 12 months, by means of a questionnaire. To analyse the data, linear and logistic regression analyses were performed. Results The intervention had a statistically significant beneficial effect on snack intake (β-1.9, 95%CI -3.7; -0.02) and fruit intake (β 1.7, 95%CI 0.6; 2.9) at 6 months. The effect on snack intake was sustained until 12 months; 6 months after the intervention had ended (β -1.9, 95%CI -3.6; -0.2). The intervention effects on leisure time PA and metabolic equivalent-minutes were not statistically significant. The beneficial effect on smoking was statistically significant at 6 (OR smoking 0.3, 95%CI 0.1;0.7), but not at 12 months (OR 0.8, 95%CI 0.4; 1.6). Conclusions Beneficial effects on smoking, fruit, and snack intake can be achieved by an individual-based lifestyle intervention among male construction workers with an elevated risk of CVD. Future research should be done on strategies to improve leisure time PA and on determinants of maintenance of changed behavior. Considering the rising prevalence of unhealthy lifestyle and CVD, especially in the aging population, implementation of this intervention in the occupational health care setting is recommended. Trial registration Current Controlled Trials ISRCTN60545588